Training principles: Evaluation of modes and methods of resistance training - A coaching perspective - Stone, M. H.; Plisk, S.; Collins, D. (Sports Biomechanics, 2002)
Current information and evidence indicate that for most activities free weight training can produce superior results compared to training with machines, particularly when the free weight training involves complex, multi-joint exercises. A number of reasons can account for the superiority of free weights; the major factor deals with mechanical specificity. Mechanical specificity is concerned with appropriate movement patterns, force application and velocity of movement. Considering the available evidence that adherence to specificity of exercise and training can result in a greater transfer of training effect than free weights should produce a more effective training transfer. Therefore, the majority of resistance exercises making up a training programme should include of free weight exercises with emphasis on mechanical specificity (i.e. large muscle mass exercises, appropriate velocity, contraction type etc.). Generally, machines should be used as an adjunct to free weight training and, depending upon the sport, can be used to a greater or lesser extent during various phases of the training period (preparation, pre-competition, competition).